Toward a climate mobilities research agenda: Intersectionality, immobility, and policy responses. (July 2021) - Cundill, Georgina; Singh, Chandni; Adger, William Neil; Safra de Campos, Ricardo; Vincent, Katharine; Tebboth, Mark; Maharjan, Amina
Highlights: Human mobility is a feature of everyday life and should be a cornerstone of development policy. Use-oriented mobilities research will support policy to recognize trans -local livelihoods. Intersecting social factors influencing mobility and immobility are a necessary research focus. Mobilities research is needed to unearth patterns of short-distance and in-country migration. Abstract: Mobility is a key livelihood and risk management strategy, including in the context of climate change. The COVID-19 pandemic has reinforced long standing concerns that migrant populations remain largely overlooked in economic development, adaptation to climate change, and spatial planning. We synthesize evidence across multiple studies that confirms the overwhelming preponderance of in-country and short distance rather than international migration in climate change hotspots in Asia and Africa. The emerging findings highlight the critical importance of addressing immobility and the intersecting social determinants that influence who can move and who cannot in development policy. This evidence suggests a more focused climate mobilities research agenda that includes understanding multiple drivers of mobility and multi-directional movement; intersecting social factors that determine mobility for some and immobility for others; and the implications for mobility and immobility under climate change and the COVID-19 recovery.